2022
DOI: 10.12912/27197050/152918
|View full text |Cite
|
Sign up to set email alerts
|

Review on Impact of Construction Waste Landfill on Environment and its Reutilization

Abstract: In several countries, the use of recycled coarse aggregate in construction materials is recommended; however, the use of organic matter is restricted because it can produce significant changes in compressive strength. In terms of reaching a conclusive viewpoint regarding the research topic, secondary data collection analysis has been selected. It is essential to utilize the recycled and by-products wastages to prepare alternative materials as this can be useful in generating a significant amount of fine concre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Such a higher volume of materials depends on its source from natural raw materials which on surplus utilization leads to scarcity. Such serious concerns about the scarcity of raw materials in construction and the surplus utilization of natural sources have to be addressed with alternative sustainable materials to ensure environmental integrity (Sivamani et al 2022). Limestone aggregates (LA) and recycled aggregates (RA) will be viable options under such circumstances to ensure sustainability in the construction.…”
Section: Introductionmentioning
confidence: 99%
“…Such a higher volume of materials depends on its source from natural raw materials which on surplus utilization leads to scarcity. Such serious concerns about the scarcity of raw materials in construction and the surplus utilization of natural sources have to be addressed with alternative sustainable materials to ensure environmental integrity (Sivamani et al 2022). Limestone aggregates (LA) and recycled aggregates (RA) will be viable options under such circumstances to ensure sustainability in the construction.…”
Section: Introductionmentioning
confidence: 99%
“…Landfilling concrete waste not only depletes valuable landfill space but also raises environmental concerns due to the potential leaching of pollutants. (Sivamani and Kamaleshwar, 2022) Iran, with its rapidly expanding construction sector, faces a growing problem of construction and demolition (C&D) waste. As estimated by industry experts, Iran generates nearly 120 million tons of C&D waste annually, with concrete constituting a major portion, while landfilling remains the dominant method for C&D waste disposal in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that treatments to RCA enhanced the quality of RCA. The most inferior characteristics of RCA was its increased porosity subsequent from the mortar smeared on its surface(Sivamani & Kamaleshwar 2022b, Sivamani et al 2021a). The acid impregnation and carbonation to RCA reduced its WA and enhanced the quality of RCA.…”
mentioning
confidence: 99%